2021
DOI: 10.7554/elife.62261
|View full text |Cite
|
Sign up to set email alerts
|

A pentameric protein ring with novel architecture is required for herpesviral packaging

Abstract: Genome packaging in large double-stranded DNA viruses requires a powerful molecular motor to force the viral genome into nascent capsids, which involves essential accessory factors that are poorly understood. Here, we present structures of two such accessory factors from the oncogenic herpesviruses Kaposi's sarcoma-associated herpesvirus (KSHV; ORF68) and Epstein-Barr virus (EBV; BFLF1). These homologous proteins form highly similar homopentameric rings with a positively charged central channel that binds doub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
3
12
0
Order By: Relevance
“…2B). These banding patterns of cleaved TR regions were in agreement with previous data which characterized an ORF68-KO reported by Glaunsinger et al (27, 28). Our data indicated that ORF7 plays a critical role in TR cleavage during lytic infection-induced viral DNA replication.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2B). These banding patterns of cleaved TR regions were in agreement with previous data which characterized an ORF68-KO reported by Glaunsinger et al (27, 28). Our data indicated that ORF7 plays a critical role in TR cleavage during lytic infection-induced viral DNA replication.…”
Section: Resultssupporting
confidence: 93%
“…Next, we asked whether the KSHV ORF7 cleaves the KSHV genome, thus contributing to KSHV terminase activity. To address this question, the cleavage of replicated KSHV DNA containing tandemly repeated genomes was detected by Southern blotting according to the method established by Glaunsinger et al (27, 28) with slight modifications (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Orf50 encodes the replication and transcription activator protein, which initiates viral lytic gene expression 35 . Orf68 encodes a packaging protein that assists in moving the newly replicated viral genomes to the packaging motor, where they are loaded into capsids 36 . Orf73 encodes for the latency-associated nuclear antigen that is required for the establishment and maintenance of latent infection 37,38 .…”
Section: Resultsmentioning
confidence: 99%
“…Orf50 encodes the replication and transcription activator protein, which initiates viral lytic gene expression 36 . Orf68 encodes a packaging protein that assists in moving the newly replicated viral genomes to the packaging motor, where they are loaded into capsids 37 . Orf73 encodes for the latency-associated nuclear antigen that is required for the establishment and maintenance of latent infection 38,39 .…”
Section: Abcs Are Dispensable For the Control Of Acute Infection And ...mentioning
confidence: 99%